PELAYANAN PUBLIK BERBASIS GOOD GOVERNANCE ( Studi tentang Akuntabilitas dan Transparansi dalam Pelayanan KTP di Kecamatan Sukolilo Kota Surabaya ) - Thetool, Yonas; Indartuti, Endang; Soenarjanto, Bagoes (Universitas 17 Agustus 1945 Surabaya, 2017)
The phenomenon of public service today is very rampant with problems by the bureaucrats who are less responsible, resulting in service to the community becomes not maximal, and people become unconvinced with the government bureaucracy. The presence of Good Governance is expected to be able to restore public trust to the government bureaucracy. Where Good Governace principles such as Accountability and Transparency are needed. The purpose of this study is To Know the Level of Accountability and Transparency in District Sukolilo Surabaya in the Service ID card. The research method used is to use descriptive research form using qualitative approach. Descriptive research will present data, analyze, interpret, and made conclusions from research conducted by the author. Based on the result of the research, it can be concluded that Accountability in ID card Service in Sukolilo Subdistrict of Surabaya City is good, where performance accountability indicator, cost accountability and accountability of service product have been appraised by society as respondent. Transparency in ID card service in Kecamatan Sukolilo Surabaya is quite good where management, service and service indicators, service procedures, service charge details, authorized and responsible officials, service standards, service promise and service location are considered good enough, but at Indicator of service information and service completion time is still considered not good by the community as respondents.Â Keywords : Public Service, Good Governance, Accountability and Transparency.